The Sustainability of Plant Uses on Sumbawa Island since the 13th Century - Juliawati, Ni Putu Eka; Ati Rati Hidayah; Aldhi Wahyu Pratama; Geria, I Made Geria; Ruly Setiawan; Luh Suwita Utami; Rochtri Agung Bawono; Abu Muslim; I Nyoman Rema; Gusti Ngurah Jayanti; I Ketut Sudharma Putra; Zuccarello, Vincenzo; et al. (Ethnobotany Research and Applications, 2025)
Background: The contemporary use of plants signifies humanity’s adaptive strategies to its environment—a phenomenon that has persisted since the inception of human civilization. This study investigates historical plant use on Sumbawa Island, based on research conducted at the Doro Mpana and Tambora archaeological sites, which date back to the 13th and 19th centuries, respectively. The objective of this study is to elucidate the historical use of plants and their ongoing sustainability, drawing upon archaeobotanical and ethnobotanical data from Sumbawa Island. Methods: Primary data for this investigation were garnered through excavation, encompassing microbotanical evidence (phytoliths) from the Doro Mpana site and macrobotanical remains from the Tambora site. Secondary data from ethnobotanical publications, were integrated to enhance understanding of the continuity of plant use in Sumbawa Island. The analysis employed a side-by-side comparative method, systematically juxtaposing attributes through tabulation to assess the sustainability of plant use across the two sites. Results: The use of flora from the Arecaceae, Euphorbiaceae, Poaceae, and Zingiberaceae families, as documented at the Doro Mpana site from the 13th century, persists, though it has evolved. The plant species identified at the Tambora site from the 19th century—including bamboo (Bambusoideae), betel leaf (Piper betle), candlenut (Aleurites moluccanus), rice (Oryza sativa), rattan (Daemonorops spp.), and sugar palm (Arenga pinnata)—continue to be employed in contemporary practices. Conclusions: The use of plants on Sumbawa Island has been shaped by environmental transformations (e.g., volcanic eruptions) and anthropogenic activities. Traditional knowledge, passed down through generations, remains pivotal in perpetuating plant use. This sustained practice not only reflects the resilience of local communities but also plays a crucial role in biodiversity conservation. By demonstrating the long-term continuity of plant use, this study contributes to a broader understanding of ecological sustainability and the cultural significance of ethnobotanical practices in island ecosystems. Keywords: Archaeobotany, ethnobotany, plant uses, Sumbawa, sustainability